Clubbable Man Essays on Eighteenth-Century Literature and Culture in Honor of Greg Clingham. - Lee, Anthony W.; Smallwood, Philip; Hopkins, David, 1948-; Rounce, Adam; Hanlon, Aaron R. (Aaron Raymond), 1982-; Walker, Robert G. (Robert Gary), 1947-; Turnbull, Gordon, 1952-; Brownley, Martine Watson; Reverand, Cedric D.; Richetti, John J. (Bucknell University Press, 2022)
Samuel Johnson famously referred to his future biographer, the unsociable magistrate Sir John Hawkins, as "a most unclubbable man." Conversely, this celebratory volume gathers distinguished eighteenth-century studies scholars to honor the achievements, professional generosity, and sociability of Greg Clingham, taking as its theme textual and social group formations. Here, Philip Smallwood examines the "mirrored minds" of Johnson and Shakespeare, while David Hopkins parses intersections of the general and particular in three key eighteenth-century figures. Aaron Hanlon draws parallels between instances of physical rambling and rhetorical strategies in Johnson's Rambler, while Cedric D. Reverand dissects the intertextual strands uniting Dryden and Pope. Contributors take up other topics significant to the field, including post-feminism, travel, and seismology. Whether discussing cultural exchange or textual reciprocities, each piece extends the theme, building on the trope of relationship to organize and express its findings. Rounding out this collection are tributes from Clingham's former students and colleagues, including original poetry.